The wage impact of trade unions in the UK public and private sectors - David G. Blanchflower; Alex Bryson (Institute for the Study of Labor (IZA), 2007)
This paper draws attention to an increase in the size of the union membership wage premium in the UK public sector relative to the private sector. We find the public sector membership wage premium is approximately double that in the private sector controlling for a full range of individual, job and workplace characteristics. Using data from the Labour Force Surveys of 1993-2006 the gap between the membership premium in the public and private sectors closes with the addition of three digit occupational controls, although significant wage premia remain in both sectors. However, using data from the Workplace Employment Relations Survey of 2004, the public sector union membership wage premium remains roughly twice the size of the private sector membership premium having accounted for workplace fixed effects, workers' occupations, their job characteristics, qualifications and worker demographics. Furthermore, the membership wage premium among workers covered by collective bargaining is only apparent in the public sector.
Keywords: 330; Trade unions; wage differentials; public and private sectors; Lohndifferenzierung; Lohnstruktur; Gewerkschaftlicher Organisationsgrad; Öffentlicher Dienst; Privatwirtschaft; Großbritannien